Avtobiografija, fikcija in roman - Koron, Alenka (Primerjalna književnost, 2003)
Autobiography, fiction and novel: on the possibilities of a genre of the 'novel as autobiography'. Kristalni čas by Lojze Kovačič (1990) and Zaznamovana by Nedeljka Pirjevec (1992) are generically mixed writings which follow the tradition of the narrative patterns of existentialism and modernism and of modernist autobiography, and deviate from the typical postmodern trends in the literature of the early 1990s. They were accepted as novels, but their syntetic genericity also corresponds to the non-fictional genre of autobiography. The article argues for the introduction of a new generic class of the 'novel as autobiography', which would include writings with a similar combination of fictional and non-fictional features. It attempts to place both texts into the new generic class - which follows the established postmodern practice that not all literature is merely fictional. The application of pragmatic model for distinguishing between fiction and non-fiction also supports this inclusion.
Keywords: Kovačič, Lojze, 1928-; Pirjevec, Nedeljka, 1932-2003; Slovene literature; slovenska književnost; literarni žanri; avtobiografije; avtobiografski roman; fiction; fikcija; literarne študije